Proceso de atención al cliente "Milán Pizzería" de la parroquia Ricaurte en el periodo 2023. - Arreaga Herrera, Jeferson Joel (2024)
The study of the "Customer Service Process of Milan Pizzeria de la Parroquia Ricaurte in the Period 2023" aims to analyze and improve customer service procedures in this popular local pizzeria. Throughout 2023, various evaluations were carried out to identify strengths and weaknesses in the care provided to clients. Milan Pizzería's customer service process ranges from receiving orders to delivering them, both at the premises and at home. Several key aspects were evaluated: the friendliness and professionalism of the staff, the efficiency of taking and delivering orders, the quality of the products, and overall customer satisfaction. Through customer surveys and interviews, valuable data was collected that revealed areas for improvement, such as the need to reduce wait time, improve order accuracy, and enhance communication between staff and customers. Additionally, it was identified that the implementation of an online ordering system could significantly optimize the customer experience. The study's findings underscore the importance of ongoing staff training in customer service skills and the use of modern technologies to streamline processes. Milan Pizzeria has implemented several strategies based on these recommendations, such as training sessions for staff and the adoption of a digital order management system.